Nature of blackbody stars - Serenelli, Aldo (2019)
A selection of 17 stars in the Sloan Digital Sky Survey, previously identified as DC-class white dwarfs (WDs), has been reported to show spectra very close to blackbody radiation in the wavelength range from ultraviolet to infrared. Because of the absence of lines and other details in their spectra, the surface gravity of these objects has previously been poorly constrained, and their effective temperatures have been determined by fits to the continuum spectrum using pure helium atmosphere models. We computed model atmospheres with pure helium and H/He mixtures and used Gaia DR2 parallaxes that are available for 16 of the 17 selected stars to analyze their physical properties.We find that the atmospheres of the selected stars are very probably contaminated with a trace amount of hydrogen of -6 ≤ log (NH/NHe) ≤ -5.4. For the 16 stars with Gaia parallaxes, we calculate a mean stellar mass 0.606 ± 0.076 M⊙, which represents typical mass values and surface gravities (7.8 < log g < 8.3) for WDs.